Análisis formal con fines interpretativos del pasillo canta cuando me ausente y el sanjuanito vamos a casa del compositor y guitarrista ecuatoriano Marco Tulio Hidrobo para guitarra clásica - Samaniego Ortega, Johnny Marcelo (2022)
The music in Ecuador was very influenced by the arrival of the colonizers and the product of that half-breed Ecuadorian music. The most representative musical genres are the pasillo and the sanjuanito, many composers have been inspired by these genres to bring their works to life with a nationalist touch that will allow Ecuadorian music to position itself nationally and internationally. Among those composers is Marco Tulio Hidrobo, a character who is part of this studio along with two works of nationalist cut which are the pasillo "Canta cuando me aunsente" and the sanjuanito "Vamos a casa". For the development of this project, it was proposed as a general objective to carry out a formal analysis for interpretive purposes on the technical-musical elements and resources of the pasillo "Canta cuando me ausente" and the sanjuanito "Vamos a casa" by ecuadorian composer Marco Tulio Hidrobo. To do this, the respective musical analysis was developed through which the musical form of the pasillo and the sanjuanito could be identified; motifs, background, consequential, metric tone, and technical resources applied within the composition of the works and their structure within the genre. Subsequent to this, the results obtained from the development of the analyses were used for the creation of a practical technical material that led to the execution of the complex passages of the works aforementioned. It is concluded that the works of the composer Marco Tulio Hidrobo transcribed for guitar, possess a high degree of complexity, and due to lacking a method for their correct execution and interpretation, they become a weakness for students when interpreting his works. Therefore, it is recommended that teachers and guitar students consider the proposal of this research work to be part of the methods of studying guitar at an advanced level